Emergence of Empirical Antibiotic Therapy and Its Outcomes against Common Infectious Diseases: A Prospective Study Using General Practice Research Database: Promoting Rational Use of Antibiotics to Combat Antimicrobial Resistance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background In India, Antibiotic use has been increasing steadily in recent years. Increasing use of antibiotics is not categorized as problem indicative, but evidence from research works related to Drug utilization gave a statement that antibiotics are very routinely used in different inappropriate ways. Therefore, it is important to evaluate antibiotics usage to reduce prevalence of antimicrobial resistance which could be a major problem in mere future. Objective The documentary target of the present research is to assess the use of Antibiotics (Rational Irrational) in a private multi-specialty hospital, its positive and negative outcomes also, to interpose scheme from pharmacist view to encourage rational use of antibiotics to improve favorable outcomes and caliber of patients.Method It was a single centered, prospective observational study. Subjects of both genders who were indicated with antibiotic therapy and patients with comorbid pathological conditions were taken into consideration. Pediatrics, Pregnant women and surgical cases were excluded of the study. Results On assessing the results of study it was found that out of 500 cases studied which accounted for 100, ceftriaxone was highly prescribed drug followed by Pipercillin + Tazobactum. On assessing rationality, it was found that 76 of prescriptions were rationality prescribed and 24 had irrationality. Amikacin was found to be the major resistant Antibiotic. Conclusion After evaluation of above results, Rational use of antibiotic for management of infection cause by microorganisms can be achieved by performing culture sensitivity testing and is very necessary to recognizes the organism to select the appropriate antibiotic leads to decrease development of resistance, decrease cost of the therapy and decrease hospital stay. By providing awareness programs, one should minimize those problems which are common at ward level such as irrational use. Counseling should be done at ward level. Awareness programs should be launched and seminars should be conducted. Monthly News sheets and Drug brief reports about the intelligent use of antibiotics should be released through publication formats. Cost effective prescription should also be encouraged. All these facts are possible when Clinical Pharmacist work along with the physician at ward level.